Structugency: A Theory of Action - A. Kinseng, Rilus (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTVarious social theories have been developed by many social scientists to explain human action individually as well as collectively. Latetely, some theories of human action are discussed within the frame of structure and agency. However, concepts of structure, agency, and their impacts on actor’s action are still debated. This article analyzes meaning of structure, agency, and their impacts onactor’s action. Method used is reviewing and analyzing some important literatures on the topics, consists of text books and international journals. It is shown that the concepts of structure is quite diverse,covers six forms. It is also developed here a concept of agency which emphasize the ability of an actor to think and act independently according to his/her own will. More over, it is argued that structure and agency should be differentiated; thus they are dualism, not duality. Both structure and agency influence an actor’s action.Keywords: Structure, agency, action, actor, structugencyABSTRAKBeragam teori dalam ilmu sosial telah dibangun oleh para ahli untuk menjelaskan tindakan manusia baik secara individu maupun secara kolektif. Belakangan ini tindakan manusia banyak dibahas dalam bingkai perdebatan tentang struktur dan agensi. Namun demikian, ada perdebatan pula mengenai arti struktur, agensi dan kaitannya dengan tindakan aktor. Tulisan ini bertujuan untuk mengkaji pengertian struktur dan agensi serta peranannya terhadap tindakan aktor. Metode yang digunakan adalah me-review dan mengkaji literatur yang membahas topik tersebut. Kajian ini menunjukkan bahwa konsep struktur itu mempunyai beragam pengertian, mencakup enam bentuk. Sementara itu, dari beragam pengertian agensi, kajian ini mengetengahkan konsep agensi yang menekankan kemampuan seseorang (aktor/agen) untuk berpikir, bersikap dan bertindak secara independen, bebas, dan otonom, sesuai dengan kehendaknya sendiri. Kajian ini juga mengajukan argumentasi bahwa struktur dan agensi itu bersifat dualisme, dan keduanya mempengaruhi tindakan aktor.Kata kunci: Struktur, agensi, tindakan, aktor, struktugensi